2018
DOI: 10.1111/jsap.12868
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system lymphoma in 18 dogs (2001 to 2015)

Abstract: Dogs receiving any type of treatment for central nervous system lymphoma lived longer than cases described in previous historical reports. Further studies are needed to elucidate the importance of specific treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…In CNS lymphoma, antemortem diagnosis is usually based on the combination of CSF analysis, MRI findings and PARR. Histopathological confirmation, performed post‐mortem in the majority of cases, is still considered the gold standard . Although clinical signs, investigations and response to treatment supported lymphoma diagnosis in our cohort of dogs, not all of them were tested for infectious agents, as these are not considered likely in dogs that had never travelled outside the UK.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…In CNS lymphoma, antemortem diagnosis is usually based on the combination of CSF analysis, MRI findings and PARR. Histopathological confirmation, performed post‐mortem in the majority of cases, is still considered the gold standard . Although clinical signs, investigations and response to treatment supported lymphoma diagnosis in our cohort of dogs, not all of them were tested for infectious agents, as these are not considered likely in dogs that had never travelled outside the UK.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, cytarabine remains a mainstay of treatment of CNS lymphoma in humans . Recently, LaRue et al reported outcomes in 18 dogs with primary CNS lymphoma treated with a variety of different modalities, including four dogs receiving cytarabine, two of which received the drug intrathecally . As only 15% of cytosine arabinoside is found to concentrate in the CSF compared with plasma concentrations in healthy dogs, intrathecal administration may be a way to enhance efficacy while improving the toxicity profile .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations